Risk Factors for Incident Hospitalized Heart Failure With Preserved Versus Reduced Ejection Fraction in a Multiracial Cohort of Postmenopausal Women. (October 2016) - Eaton, Charles B.; Pettinger, Mary; Rossouw, Jacques; Martin, Lisa Warsinger; Foraker, Randi; Quddus, Abdullah; Liu, Simin; Wampler, Nina S.; Hank Wu, Wen-Chih; Manson, JoAnn E.; Margolis, Karen; Johnson, Karen C.; et al.
Abstract : Background—: Heart failure is an important and growing public health problem in women. Risk factors for incident hospitalized heart failure with preserved ejection fraction (HFpEF) compared with heart failure with reduced ejection fraction (HFrEF) in women and differences by race/ethnicity are not well characterized. Methods and Results—: We prospectively evaluated the risk factors for incident hospitalized HFpEF and HFrEF in a multiracial cohort of 42 170 postmenopausal women followed up for a mean of 13.2 years. Cox regression models with time-dependent covariate adjustment were used to define risk factors for HFpEF and HFrEF. Differences by race/ethnicity about incidence rates, baseline risk factors, and their population-attributable risk percentage were analyzed. Risk factors for both HFpEF and HFrEF were as follows: older age, white race, diabetes mellitus, cigarette smoking, and hypertension. Obesity, history of coronary heart disease (other than myocardial infarction), anemia, atrial fibrillation, and more than one comorbidity were associated with HFpEF but not with HFrEF. History of myocardial infarction was associated with HFrEF but not with HFpEF. Obesity was found to be a more potent risk factor for African American women compared with white women for HFpEF ( P for interaction=0.007). For HFpEF, the population-attributable risk percentage was greatest for hypertension (40.9%) followed by obesity (25.8%), with the highest population-attributable risk percentage found in African Americans for these risk factors. Conclusions—: In this multiracial cohort of postmenopausal women, obesity stands out as a significant risk factor for HFpEF, with the strongest association in African American women. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00000611. Abstract : Supplemental Digital Content is available in the text.